Teacher Profession and Professionalism - Ainayya Husna; Anisa Oktaviana; Fery Fadli; Mahariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In the current era, there are many teachers who have been allowed to teach in a school even though the teacher does not yet have one of the criteria as a professional teacher, namely having a diploma. Therefore researchers want to examine the professionalism of a teacher which is seen universally from existing schools. In this study, the method used is the method of meta- analysis. Meta-analysis research is a research method that involves collecting, processing, and presenting data in a systematic and objective manner. The purpose of this meta-analysis research is to examine the extent to which teacher competence refers to qualification and competency standards that have been established based on Permendiknas No. 16 of 2007.